2004
DOI: 10.1667/rr3249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplements on Space Radiation-Induced Oxidative Stress in Sprague-Dawley Rats

Abstract: Of particular concern for the health of astronauts during space travel is radiation from protons and high-mass, high-atomic-number (Z), and high-energy particles (HZE particles). Space radiation is known to induce oxidative stress in astronauts after extended space flight. In the present study, the total antioxidant status was used as a biomarker to evaluate oxidative stress induced by gamma rays, protons and HZE-particle radiation. The results demonstrate that the plasma level of total antioxidants in Sprague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…We have previously demonstrated the preventive effect of antioxidants against radiationinduced oxidative stress in vitro and in vivo, which was measured by radiation-induced reductions of serum or plasma total antioxidant status in animals (21)(22)(23)(24)28). The present study assessed the hematopoietic radioprotective efficacy of an oral formulation consisting of SeM, α-lipoic acid, NAC, vitamin C and vitamin E succinate in vivo using animal survival and immune cell counts as the end points.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have previously demonstrated the preventive effect of antioxidants against radiationinduced oxidative stress in vitro and in vivo, which was measured by radiation-induced reductions of serum or plasma total antioxidant status in animals (21)(22)(23)(24)28). The present study assessed the hematopoietic radioprotective efficacy of an oral formulation consisting of SeM, α-lipoic acid, NAC, vitamin C and vitamin E succinate in vivo using animal survival and immune cell counts as the end points.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, we reported that TBI of mice and rats with γ rays, protons or HZE particles decreased the serum total antioxidant capacity within 4 h, which was prevented by dietary supplementation with antioxidants (23,24). The antioxidant combination was formulated to provide the equivalent of 2000 mg/day, 1000 mg/day and 400 μg/day, which represent the upper limits of the RDA for vitamin C, vitamin E succinate and selenium, respectively (25).…”
Section: Introductionmentioning
confidence: 99%
“…Highly energetic heavy charged particles known as HZE particles and protons are among the most biologically significant components of space radiation. While there are many different types of cellular and molecular damage induced by HZE particles and protons, our studies have shown that these types of ionizing radiations can induce oxidative stress in cells (1)(2)(3) and animals (4)(5)(6). Oxidative stress (7) is a term that describes the biological damage of DNA, lipids and proteins by either oxygen reactive organic radicals or oxygen radicals, e.g., the hydroxyl radical.…”
Section: Introductionmentioning
confidence: 98%
“…L-Selenomethionine (SeM), N-acetyl cysteine (NAC), ascorbic acid, co-enzyme Q10, α-lipoic acid and vitamin E succinate were observed to have significant suppressive effects on space radiation-induced oxidative stress in vitro both when they were evaluated as single agents and when they were evaluated as a combination of agents (2). It has been demonstrated that this combination of antioxidant compounds is also highly effective in protecting against HZE-particle-and proton-induced cytotoxicity (15), space radiationinduced transformation in cultured human thyroid epithelial cells (3,15), and radiationinduced oxidative stress in mice and rats exposed to radiation from HZE particles, protons and γ rays (4)(5)(6). None of these agents alone can completely prevent or suppress these biological phenomena, but when used together as a combination, the agents work together to have a highly significant suppressive effect on adverse biological effects of space radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment-related changes were filtered through the Previous research have shown that that total body irradiation (TBI) of mice and rats with γ-rays (GR), protons or high-energy (HZE) particles resulted in oxidative stress that could be quantified by decreased serum total antioxidant capacity within 4 h of radiation exposure and the observed TBI-induced decrease in serum antioxidant capacity was prevented by dietary antioxidant (AOX) supplementation. 11,12 Furthermore, dietary AOX supplementation prior to or after exposure to GR TBI was an effective countermeasure in limiting hematopoietic cell depletion, promoting hematopoietic cell recovery, and ultimately, improving mice survival. 1 Proton radiation (PR) has generated interest for its capacity to selectively increase radiation dose to the tumor while lowering the dose to surrounding normal tissues.…”
Section: Resultsmentioning
confidence: 99%